Career Coaching: Developing a Constructive Mindset and Ethical Conduct in the Realm of Employment from a Young Age - Dewi Anggraini; Marisya Pratiwi; Rachmawati Rachmawati; Amalia Juniarly (Altifani Journal: International Journal of Community Engagement, 2024)
The current era in which the world of work is evolving into 4.0 requires businesses to be more competitive; therefore, human resources are essential to this end. Effective employee performance positively influences the company's overall performance. This pertains to the correlation between good attitudes and behaviours in employees, leading to increased engagement in work, heightened motivation, and job satisfaction. Developing a positive attitude and behaviour in individuals from a young age is crucial. Students, as future human resources entering the workforce, should be equipped with abilities and character that align with the company's requirements. Through this career coaching programme, students are expected to develop insight, knowledge, and positive attitudes and behaviours related to the workplace from an early age by implementing them in an educational environment. 63 persons from the 1st-semester students of the Psychology Study Programme at Sriwijaya University participated in this activity. This service activity is aligned with the industrial and organisational psychology courses that participants will complete in semester 3. The outcomes of this activity may be determined through pre and post-evaluation, revealing that 95.3% of participants grasp the career coaching activity effectively.